Characterization and optimization of bilosomes for oral vaccine delivery. (April 2013) - Wilkhu, Jitinder S.; McNeil, Sarah E.; Anderson, David E.; Perrie, Yvonne
<x xml:space="preserve">Abstract</x> Oral vaccines offer significant benefits due to the ease of administration, better patient compliance and non-invasive, needle-free administration. However, this route is marred by the harsh gastro intestinal environment which is detrimental to many vaccine formats. To address this, a range of delivery systems have been considered including bilosomes; these are bilayer vesicles constructed from non-ionic surfactants combined with the inclusion of bile salts which can stabilize the vesicles in the gastro intestinal tract by preventing membrane destabilization. The aim of this study was to investigate the effect of formulation parameters on bilosome carriers using Design of Experiments to select an appropriate formulation to assess in vivo. Bilosomes were constructed from monopalmitoylglycerol, cholesterol, dicetyl phosphate and sodium deoxycholate at different blends ratios. The optimized bilosome formulation was identified and the potential of this formulation as an oral vaccine delivery system were assessed in biodistribution and vaccine efficacy studies. Results showed that the larger bilosomes vesicles (~6 µm versus 2 µm in diameter) increased uptake within the Peyer's patches and were able to reduce median temperature differential change and promote a reduction in viral cell load in an influenza challenge study.